1989
DOI: 10.1021/j100343a037
|View full text |Cite
|
Sign up to set email alerts
|

Absolute rates of vacuum-ultraviolet photochemical deposition of organic films

Abstract: Absolute rates of vacuum-ultraviolet photochemical deposition of thin films from high molecular weight siloxane and phthalate precursors have been measured in molecular beam experiments using sensitive quartz crystal microbalance detection. Depositions were carried out under conditions of surface temperature and molecular flux for which bulk condensation would not occur.The deposition rate demonstrated an inverse dependence on substrate temperature, weak dependence on photolysis wavelength (below 200 nm), a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 2 publications
2
10
0
Order By: Relevance
“…The activation energy for desorption can be determined from FEBIP experiments by measuring the deposition rate as a function of substrate temperature and constructing an Arrhenius plot. Christy measured E des in a FEBIP experiment for a siloxane (tetramethyl tetraphenyl trisiloxane, DC-704 pump oil) and found that the value found from the FEBIP experiment underestimates the desorption energy by a factor of two to three compared to reference values [1415]. Li et al have performed the same measurement for WF 6 [16] and found a desorption energy that was three to five times lower than expected.…”
Section: Introductionmentioning
confidence: 99%
“…The activation energy for desorption can be determined from FEBIP experiments by measuring the deposition rate as a function of substrate temperature and constructing an Arrhenius plot. Christy measured E des in a FEBIP experiment for a siloxane (tetramethyl tetraphenyl trisiloxane, DC-704 pump oil) and found that the value found from the FEBIP experiment underestimates the desorption energy by a factor of two to three compared to reference values [1415]. Li et al have performed the same measurement for WF 6 [16] and found a desorption energy that was three to five times lower than expected.…”
Section: Introductionmentioning
confidence: 99%
“…Besides affecting light transmission loss, the aromatic groups in DC704 also impact photodeposition, fixing, and darkening. The rates of those photochemical processes are a function of many parameters including the contaminant concentration at the surface and their ability to absorb photons 11 . Once photons are absorbed, presumably leading to radical formation, the stability of those reactive species will be determined by the functional groups of the contaminant.…”
Section: Light Absorptionmentioning
confidence: 99%
“…[1][2][3][4][5] In view of this a great deal of work has been done in measuring photofixing rates for a variety of materials as a function of illumination wavelength and substrate temperature. Some in-situ measurements of the reflection /transmission changes of the substrate-film as a function of film deposition have also been performed.…”
Section: Introductionmentioning
confidence: 99%